2005
DOI: 10.1007/s11167-005-0306-z
|View full text |Cite
|
Sign up to set email alerts
|

Polythermal Study of the Systems M(ClO4)2-H2O (M2+ = Mg2+, Ca2+, Sr2+, Ba2+)

Abstract: The solubility polytherms in the systems for which the cryoscopic data are lacking were measured. The structural models of the electrolyte solutions were discussed on the basis of the solubility polytherms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
66
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 2 publications
6
66
1
Order By: Relevance
“…In NaClO 4 solutions, FPDs measured by Hennings et al (2013) and Freeth (1924) sometimes differ from our measurements by up to six degrees at the same molality. In Ca(ClO 4 ) 2 solutions, the data of Pestova et al (2005) is scattered above and below our dataset by an average of about one degree. The data of Dobrynina et al (1984) is also consistent with our dataset at low molality, but differs significantly from both our study and Pestova et al (2005) above $6 mol kg À1 .…”
Section: Ice and Salt Solubility Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…In NaClO 4 solutions, FPDs measured by Hennings et al (2013) and Freeth (1924) sometimes differ from our measurements by up to six degrees at the same molality. In Ca(ClO 4 ) 2 solutions, the data of Pestova et al (2005) is scattered above and below our dataset by an average of about one degree. The data of Dobrynina et al (1984) is also consistent with our dataset at low molality, but differs significantly from both our study and Pestova et al (2005) above $6 mol kg À1 .…”
Section: Ice and Salt Solubility Resultsmentioning
confidence: 81%
“…Our equilibrium method of measuring FPD and solubility is in contrast to dynamic methods (e.g. Pestova et al, 2005), in which the temperature is raised or lowered until the solid phase dissolves or precipitates. To prevent the salt solutions from corroding the copper, the interior of the reaction vessel (75 cm 3 volume) was lined with polyethylene.…”
Section: Methods: Fpd and Solubility Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…While this previous work on microscopic samples demonstrated that perchlorate deliquescence should be thermodynamically favored under certain Martian conditions, other experimental results have indicated that the process is not rapid enough to allow for a substantial amount of bulk deliquescence during the Martian diurnal cycle [Fischer et al, 2014]. There also exists some question as to the exact nature of the eutectic temperature of the magnesium perchlorate-water system with previously measured freezing point depressions ranging from À68°C [Pestova et al, 2005] to À57°C [Stillman and Grimm, 2011]. It has even been suggested that magnesium perchlorate brines could remain as a supercooled liquid throughout the entirety of the coldest Martian nights [Toner et al, 2014b].…”
Section: Introductionmentioning
confidence: 91%